2010
DOI: 10.1186/1479-5876-8-35
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of T-cell receptor repertoire restriction in blood and tumor tissue of colorectal cancer patients

Abstract: Several immunotherapeutic approaches rely on antigen-specific T-cells. Restrictions in the T-cell receptor (TCR) repertoire were reported as indicator of anti-tumor cytotoxic T-lymphocyte (CTL) response in various tumor entities. It is unclear yet whether a TCR restriction in peripheral blood mirrors the tumor compartment. We compared the expression of TCR Vβ-families for the quantification of TCR repertoire alterations in blood and tissue samples from patients with colorectal carcinoma. Blood samples from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…Like Ochsenreither et al [24] we find that the V gene usage and CDR3 length are conserved between these two tissue types (Fig. 3).…”
Section: Discussionsupporting
confidence: 87%
“…Like Ochsenreither et al [24] we find that the V gene usage and CDR3 length are conserved between these two tissue types (Fig. 3).…”
Section: Discussionsupporting
confidence: 87%
“…However, to the best of our knowledge, no previous studies have investigated the clonality or functionality of the T cells. In the present study, next-generation sequencers were used to comprehensively analyze the TCR repertoire in the tissue and blood samples obtained from advanced CRC patients that had been treated with cancer peptide vaccines in combination with oxaliplatin-based chemotherapy, and it was confirmed that the T cell repertoires in tissues varied from the T cell repertoires in blood samples, as previously described ( 22 – 27 ). Although previous studies only analyzed TCR clonotypes.…”
Section: Discussionsupporting
confidence: 76%
“…Given the variation in the TCRB repertoire diversity between mucosal tissue and matched tumor tissue, we tested to see if other measures of TCRB repertoire were divergent between the two tissue types. Like Ochsenreither et al [24] we find that the V gene usage and CDR3 length are conserved between these two tissue types (Fig. 3).…”
Section: Discussionsupporting
confidence: 88%